Zygophylax levinseni - Gu, Zhangjie; Ruthensteiner, Bernhard; Moura, Carlos J.; Liu, Lihua; Zhang, Rui; Song, Xikun (Zenodo, 2022)
ZYGOPHYLAX LEVINSENI (SAEMUNDSSON, 1911) (FIG. 11) Zygophylax levinseni : Vervoort, 2006: 240–242, fig. 16 (synonymy). Type locality: Near the Vestmannaeyjar Archipelago, Iceland; 510 m. Specimens examined: Five colonies from the Gulf of Cadiz, two fertile; see details in Supporting Information, Table S1. Molecular sequences: 16S rRNA (Moura et al. , 2008, 2012); 18S rRNA and 28S rRNA genes (this study); see sequence details in Supporting Information, Table S3. Measurements: See details in Supporting Information, Table S2. Description: Trophosome. Colonies erect, up to 4.5 cm in height (Fig. 11A). Hydrocaulus straight, polysiphonic, unsegmented, branching. Hydrocladia coplanar, dichotomously branched, straight, monosiphonic (Figs 11A, B), with irregular nodes (Fig. 11E), forming angles of 30°–60° with the hydrocaulus (Fig. 11A), axillary hydrothecae present at branching points (Fig. 11E). Hydrothecae arranged alternately in two planes forming angles of 30°–60° (Fig. 11B); borne on moderately long pedicels, tubular, distal part straight or slightly curved, one or two oblique diaphragms basally (Fig. 11D), margin slightly everted, with one to three renovations (Fig. 11D–F). One nematotheca present on apophyses of hydrocladia (Fig. 11F, H). Gonosome: Gonothecae clustering into coppiniae encircling the hydrocaulus (Fig. 11C), with abundant protective tubes, one nematotheca observed on the base of one protective tube (Fig. 11G, I). Gonothecae free from one another, elliptical, tapering basally, apices with two lateral, curved tubes (Fig. 11C, G). Distribution: Gulf of Cadiz (Moura et al. , 2008; this study); south of Iceland (Saemundsson, 1911); the Azores region (Leloup, 1940); near the coast of Rabat, Morocco (Ramil & Vervoort, 1992); one tropical Atlantic locality, south of Cape Verde Islands (Vervoort, 2006); Madeira (Moura et al. , 2012). Remarks: Zygophylax tottoni Rees & Vervoort, 1987 resembles Z. leviseni by the hydrothecal morphology, but Z. leviseni has comparatively more numerous and smaller ...